(untitled) (Historia, 2021)
1. Murray, A. H.: The Poli ical Philosophy of J. A. de Mist, Commissiollcr-Gelleral at the Cape, 1803-1805. A Study in Political Pluralism 2. Scholtz, G. D.: Die Stryd om die Wereld 3. Bouman, P. J.: In de ban der Geschiedenis